Pengaruh Kecerdasan Buatan(AI) Dan Big Data Terhadap Kinerja Karyawan - Bambang Widjanarko Susilo; Agustinus Wardi; Sri Heneng Prasastono (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2022)
Main Problem: There are differences in the influence of AI and Big Data on employee performance in previous research. Objective: Focus research by reviewing and analyzing whether Artificial Intelligence or AI has an influence on employee performance. Next, analyze whether Big Data affects employee performance. Originality: The Influence of AI and Big Data on Employee Performance. Method: To select the research sample, the proportional area random sampling method and regression equation were used to process the data with the help of the SPSS application. Results: In this research and discussion, it can be concluded that AI Big Data has an influence on the performance of employees at PT. Widya Robotics Yogyakarta, General Ahmad Yani International Airport Semarang, PT. Global Data Inspiration Yogyakarta.